2020
DOI: 10.1101/2020.10.21.349357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of negative regulation of NF-κB by N4BP1

Abstract: Many immune responses depend upon activation of NF-κB, a key transcription factor in the elicitation of a cytokine response. Here we demonstrate that N4BP1 inhibited TLR-dependent activation of NF-κB by interacting with the NF-κB signaling essential modulator (NEMO, also known as IκB kinase γ) to attenuate NEMO-NEMO dimerization or oligomerization. The UBA-like (ubiquitin associated-like) and CUE-like (ubiquitin conjugation to ER degradation) domains in N4BP1 mediated the interaction with the NEMO COZI domain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…FunRich analysis demonstrated interactions among these proteins, with a focus on CREB1 (Figure -S12B). On the basis of published literature that implicated these four proteins in the regulation of the nuclear factor-κB (NF-κB) signaling pathway, [26][27][28][29] the protein-protein interaction (PPI) network and schematic diagram that contained key proteins (NEDD4, IKBKG, CACTIN, and OTUD7B) suggested that CREB1, DEAF1, and N4BP1 might negatively regulate NF-κB signaling (Figure S12C).…”
Section: Survival Analysis and Functional Enrichment For N4bp1 And Cr...mentioning
confidence: 99%
“…FunRich analysis demonstrated interactions among these proteins, with a focus on CREB1 (Figure -S12B). On the basis of published literature that implicated these four proteins in the regulation of the nuclear factor-κB (NF-κB) signaling pathway, [26][27][28][29] the protein-protein interaction (PPI) network and schematic diagram that contained key proteins (NEDD4, IKBKG, CACTIN, and OTUD7B) suggested that CREB1, DEAF1, and N4BP1 might negatively regulate NF-κB signaling (Figure S12C).…”
Section: Survival Analysis and Functional Enrichment For N4bp1 And Cr...mentioning
confidence: 99%